MY FASHION JOURNEY DALAM KARYA SENI GRAFIS LINOCUT - Reza Yogi Saputri; Nunuk Nur Shokiyah (Texture:Art and Culture Journal, 2022)
The experience of the journey process of finding a character in fashion is done with a sense of comfort, courage, happiness. The creation of this work aims to create works of art with sources of inspiration: The journey process of finding characters in fashion and Fashion Storytelling, explaining the concept, creation process, and description of graphic art works. The process of creating this work of art uses the L.H. Chapman, that in the creation of works there are three stages, namely Finding ideas, perfecting and Visualization The process of traveling in fashion is expressed in the work of Graphic Art by processing elements and principles of visual composition, through the study of the process and concept of the creation of the work, using high print or cut techniques in linoleum on paper with 2 techniques, namely puzzle technique and reduction technique.